Evolution of Desire : a Life of René Girard. - Haven, Cynthia L. (Studies in violence, mimesis, and culture., 2018)
René Girard (1923-2015) was one of the leading thinkers of our era-a provocative sage who bypassed prevailing orthodoxies to offer a bold, sweeping vision of human nature, human history, and human destiny. His oeuvre, offering a "mimetic theory" of cultural origins and human behavior, inspired such writers as Milan Kundera and J. M. Coetzee, and earned him a place among the forty "immortals" of the Académie Française. Too often, however, his work is considered only within various academic specializations. This first-ever biographical study takes a wider view. Cynthia L. Haven traces the evolution of Girard's thought in parallel with his life and times. She recounts his formative years in France and his arrival in a country torn by racial division, and reveals his insights into the collective delusions of our technological world and the changing nature of warfare. Drawing on interviews with Girard and his colleagues,Evolution of Desire: A Life of René Girardprovides an essential introduction to one of the twentieth century's most controversial and original minds.